Projeto aquícola: empresa especializada em logística e transporte de peixes ornamentais - Silva, Gisele de Souza (Universidade Estadual Paulista (Unesp), 2024)
Aquarium farming, or ornamental fish farming, is a widely spread global hobby and an expanding pet market niche, with great economic potential. Brazil stands out as one of the main producers of ornamental fish in the world, serving both the domestic and international markets. With thousands of producers spread across the country, especially concentrated in the southeast region, there is a growing demand for technical assistance to improve product quality and optimize marketing. presents an aquaculture project proposal from a company focused on developing solutions to optimize the logistics of transporting ornamental fish, with a focus on specialized consultancy for national producers. The solutions aim to facilitate the connection between producers and buyers, ensuring the integrity of production to the final consumer. Nowadays, fish welfare techniques can be used with the use of NaCl, among others. The transport of ornamental fish is important as it involves complex challenges. There are full adjustments necessary so that the specimens can be transported. We use Normative Instructions to compose this work, so that it helps and provides the necessary focus for the transparency of this field of activity. Specialized consultancy for producers is an important point that we address. From the most basic proposal to advanced/complete.

A aquariofilia, ou criação de peixes ornamentais, é um passatempo amplamente difundido em nível global e um nicho de mercado pet em expansão, com grande potencial econômico. O Brasil se destaca como um dos principais produtores de peixes ornamentais do mundo, atendendo tanto ao mercado interno quanto ao internacional. Com milhares de produtores espalhados por todo o país, especialmente concentrados na região sudeste, há uma crescente demanda por assistência técnica para melhorar a qualidade dos produtos e otimizar a comercialização. apresenta uma proposta de projeto aquícola de uma empresa voltada ao desenvolvimento de soluções para otimizar a logística de transporte de peixes ornamentais, com foco em consultorias especializadas para produtores nacionais. As soluções visam facilitar a conexão entre produtores e compradores, garantindo a integridade da produção até o consumidor final. Hodiernamente podem ser utilizadas técnicas de bem-estar para os peixes com o uso do NaCl dentre outras. Faz-se importante o transporte de peixes ornamentais como complexo que envolve desafios. Há regularizações integrais necessárias para que os exemplares possam ser transportados. Utilizamos Instruções Normativas para compor esse trabalho, para que auxilie e dê o foco necessário para a transparência de tal ramo de atividade. A consultoria especializada para os produtores é um ponto importante que tratamos. Desde a proposta mais básica à avançada/completa.
Aquicola project: company specialized in logistics and transport of ornamental fish
Keywords: Ornamental; Comércio; Consultoria; Consumidor; Consultancy; Commerce; Ornalmental; Consumer